Penelusuran Sumber Definisi SyÄáº“ Al-SyÄfiâ€™Ä«: Sebuah Kajian Bibliografis - Dalimunthe, Reza Pahlevi; Masri, Dedi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
One of the rules of the validity of the Prophet's traditions is to avoid shÄáº“. The definition of shÄáº“ according to al-Shafi'Ä« (150-204 H) is a single narrator whose history of hadith contradicts with many other narrators. The majority of hadith scholars such as Ibn al-á¹¢alÄh (577-643 H), chose the definition over the others. This article focuses on searching the bibliographic source for the definition of shÄáº“ al-ShÄfiâ€™Ä« with an intertext approach. The object is the works of al-Shafi'Ä« in the field of hadith and a variety of hadith science literature which includes the definition of shÄáº“. This study shows that hadith experts generally agree with the definition of shÄáº“ al-Shafi'Ä« because it is easier to apply than other definitions. However, they did not clearly mention the title of al-Shafi'i's essay which he referred to, causing misunderstanding as if the source of the definition of shÄáº“ was Ibn al-á¹¢alÄá¸¥, not al-Shafi'Ä«. One of these misconceptions stems from the unclear reference of Ibn al-á¹¢alÄá¸¥ himself. This study shows that the bibliographic results of al-Shafi'i's works and transmission lines of definitions are found that the definition of al-Shafi is not found in al-Risalah, but is sourced from al-Manafib al-Shafi al-BaihaqÄ«